A new fluorescent probe based on quinoline for detection of Al3+ and Fe3+ with "off–on–off" response in aqueous solution. Issue 102 (21st October 2016) - Dai, Yanpeng; Liu, Xiaoyan; Wang, Peng; Fu, Jiaxin; Yao, Kun; Xu, Kuoxi
Abstract : A new quinoline-based fluorescent probe has been designed and synthesized. It showed highly selective relay recognition of Al 3+ and Fe 3+ via a fluorescence "off–on–off" mechanism by central metal displacement. Abstract : A new quinoline-based fluorescent probe1 has been designed and synthesized. Fluorescence emission spectra of the probe showed red-shift and obvious enhancement of fluorescent intensity upon the addition of Al 3+ (turn-on).1 –Al 3+ showed high selectivity for Fe 3+ over other metal ions, and eliminated the interference of Al 3+ during Fe 3+ detection (turn-off). It showed highly selective relay recognition of Al 3+ and Fe 3+ via a fluorescence "off–on–off" mechanism. Fluorescence spectra indicated that the response of1 –Al 3+ to Fe 3+ was caused by central metal displacement. The detection limits for the analysis of Al 3+ and1 –Al 3+ –Fe 3+ ions were calculated to be 2.20 × 10 −6 M and 1.96 × 10 −5 M, respectively. Living HeLa cell imaging studies revealed that the probe was cell-permeable and it could be used to detect intracellular Al 3+ and Fe 3+ ions.